Genetically-engineered Salmonella typhimurium expressing FGF21 promotes neurological recovery in ischemic stroke via FGFR1/AMPK/mTOR pathway - Dongchen Xu; Min Wen; Bingwa Lebohang Anesu; Xijun Chen; Yuhao Chen; Wenqi Qian; Chenguang Yang; Jin Hai Zheng; Yinan Zhou; Haoqi Ni; Kunlin Jin; Qichuan Zhuge; et al. (Journal of Neuroinflammation)
Abstract Background Ischemic stroke (IS) remains a leading cause of mortality and disability, with limited therapeutic options due to poor drug delivery to ischemic lesions. To address this challenge, an engineered Salmonella based therapeutic method for targeted drug delivery and long-term treatment is herein designed to mitigate ischemic damage. Methods We engineered an attenuated luminescent Salmonella typhimurium (S.t -ΔpG) strain with an L-arabinose-inducible pBAD system to secrete bioactive FGF21. C57BL/6 mice were used to to measure neuron apoptosis and the activity of immune cells following IS induction plus S.t-ΔpG injection. Bioluminescence imaging was applied for bacterial colonization. ELISA and glucose uptake assays were performed to detect FGF21 secretion and the bioactivity. Neurological tests, TTC staining, and TUNEL labeling were used to assess the therapeutic effects of barterially secreted FGF21. Immunofluorescence assay of FGF21/FGFR1 dominant pathway was explored to investigate neuroprotective mechanism, while IBA-1 staining, CD3/CD68 immunostaining, cytokine profiling, and hepatorenal histopathology were detected to evaluate biosecurity. Results S.t-ΔpGFGF21 selectively colonized peri-infarct regions and secreted functional FGF21, reducing neurologic deficits (48%) and infarct volume (46%) versus controls (p < 0.01). Mechanistically, immunofluorescence demonstrated that bacterially secreted FGF21 activated neuronal FGFR1/AMPK/mTOR pathway to enhance autophagy, whereas autophagy inhibition abolished its neuroprotection. Further, bacterial exclusion from neuron was validated via MAP2/NeuN plus Salmonella co-staining in primary neuron cells and brain tissue. Critically, CD3/CD68 immunostaining, serum cytokine profiling, and hepatorenal histopathology confirmed the long-term biosafety of this approach. Conclusion Our study presents a novel, Salmonella - based platform for targeted and sustained FGF21 delivery, offering a promising therapeutic strategy for ischemic stroke with robust efficacy and minimal systemic toxicity.